EXAMINATION OF THE MARKET CONCENTRATION, PROFITABILITY AND EFFICIENCY OF CORPORATE AGRICULTURAL ENTERPRISES IN THREE HUNGARIAN REGIONS - Pataki, László; Lakatos, Vilmos (Acta Carolus Robertus, 2021)
Since the change of regime, significant changes have taken place in the Hungarian agricultural sector. These changes affected the ownership structure, market conditions and, last but not least, the capital structure of agricultural enterprises and their income situation. Accession to the European Union has also had a significant impact on the income situation of agricultural enterprises. In our study, we examine the profitability situation of the corporate agricultural enterprises of 3 Hungarian statistical regions in relation to the period between 2012 and 2018, we try to reveal the differences by region and their possible reasons. Our research also covers the development of the efficiency of the examined business circle, and we also dealt with the determination of the degree of market concentration. We found that the level of market concentration was low in the sample examined, while profitability and efficiency deteriorated, albeit to a differentiated extent by region.
Keywords: statistical regions; agricultural joint ventures; market concentration; profitability; efficiency